2013
DOI: 10.1186/1471-2458-13-1095
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evidence synthesis of employees’ views of workplace smoking reduction or cessation interventions

Abstract: BackgroundThe need to reduce smoking rates is a recognised public health policy issue in many countries. The workplace offers a potential context for offering smokers’ programmes and interventions to assist smoking cessation or reduction. A qualitative evidence synthesis of employees’ views about such programmes might explain why some interventions appear effective and others not, and can be used to develop evidence-based interventions for this population and setting.MethodsA qualitative evidence synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
17
0
3
Order By: Relevance
“…High nicotine dependence strongly predicted failure to quit smoking 15 or the cost-effectiveness of smoking cessation programmes. 20 As an employee who feels ready and capable of changing his behaviour has needs and preferences that significantly differ from one who is not at that stage, 21 workplace smoking cessation interventions that employ only one method 22 do not generally have positive effects on the smoking cessation attempts of all employees. The current results showed that nicotine dependence is related to motivators for smoking cessation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…High nicotine dependence strongly predicted failure to quit smoking 15 or the cost-effectiveness of smoking cessation programmes. 20 As an employee who feels ready and capable of changing his behaviour has needs and preferences that significantly differ from one who is not at that stage, 21 workplace smoking cessation interventions that employ only one method 22 do not generally have positive effects on the smoking cessation attempts of all employees. The current results showed that nicotine dependence is related to motivators for smoking cessation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple effective workplace-based smoking cessation interventions are already available, such as group behavior theory, individual counselling, NTR provision, and comprehensive programs (12). According to a qualitative evidence synthesis on employees views on workplace smoking cessation interventions, workplace smoking cessation inventions should have multiple components in order to facilitate employees in various phases of the cessation process, since needs and preferences can vary considerably between workers (81). A study simulating the effect of a worksite smoking cessation program found that potential savings from reduced sickness absence by far exceeded the program costs (80).…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…A qualitative evidence synthesis of workplace smoking interventions concluded that workplace interventions should employ a range of different elements because different employees have different requirements. 83 Overall, the nine BCTs that formed the basis of the Walk to Work intervention during the feasibility study appeared acceptable to participants and were retained for the main trial. However, the term 'relapse prevention' had been challenged by some participants as being inappropriate for an intervention that promotes walking.…”
Section: Chapter 5 the Walk To Work Interventionmentioning
confidence: 99%